The wakeup call of COVID-19: perceptions of crisis impacts in the real estate market - Toivonen, Saija; Sinisalo, Henrik; Uusitalo, Eini (International Journal of Strategic Property Management, 2023)
Participants in the real estate market are exposed to a variety of endogenous and exogenous crises. Because the real estate market environment is closely interconnected with the broader society and its diverse forces, the direct and indirect impacts of crises are experienced through changes in real estate market dynamics. In the future, the market environment is expected to be even more challenging, full of complexity, uncertainties, and ambiguities, which will require developing the skills, first, to learn from crises already experienced and then to foresee, prevent, or adapt to ones yet unseen. This article aims to deepen the understanding of how crisis impacts were perceived in the real estate market during the COVID-19 pandemic. The research applies a qualitative approach by interviewing 19 real estate market professionals in Finland to identify the factors influencing market dynamics, such as market sentiments, preferences, and procedures. The results will help market participants understand the diversity of crisis impacts, their interconnections, and how they are perceived. The findings contribute to the real estate literature by offering a qualitative perspective that supports individuals and organizations in developing risk and crisis management skills and contributes to building a more resilient real estate market to support communities.